1996
DOI: 10.1159/000456938
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Nociception-Related and Arterial Pressure-Related Neuronal Responses in the Nucleus Reticularis Gigantocellularis of the Rat

Abstract: The present study was undertaken to further characterize the nucleus reticularis gigantocellularis (NRGC) of the medulla oblongata in the central processing of nociceptive and cardiovascular signals, and its modulation by metenkephalin. In Sprague-Dawley rats anesthetized with pentobarbital sodium, we found that all 125 spontaneously active NRGC neurons that responded to noxious stimuli (tail clamp) also exhibited arterial pressure-relatedness. Forty neurons additionally manifested cardiac periodicity that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[16][17][18] Cholinergic neurons in the NRGC/NRGCa mainly project from the PPT, 6) and microinjections of carbachol into the PPT also produce dose-dependent antinociception. 12,19,20) In the present study, the results of the HP and TF tests showed that carbachol microinjected into the NRGC/NRGCa induced antinociception in a dose-related manner.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Cholinergic neurons in the NRGC/NRGCa mainly project from the PPT, 6) and microinjections of carbachol into the PPT also produce dose-dependent antinociception. 12,19,20) In the present study, the results of the HP and TF tests showed that carbachol microinjected into the NRGC/NRGCa induced antinociception in a dose-related manner.…”
Section: Discussionmentioning
confidence: 99%